La repercussió de l'obra de Lorenzo Palmireno en la Filologia Catalana - Veny, Joan (Caplletra. Revista Internacional de Filologia, 2015)
It is always useful to set bounds to a semantic field when attempting to discuss lexical transmission. Once our attention is phocused on the names of birds collected by Palmireno in his Vocabulario del Humanista (1569), the influence of Belon, Gesner and specially of Joan B. Agnes becomes evident. On the other hand, it is also evident that the Catalan lexicographer Pere Torra (17th century) used in a rather indiscriminate manner Palmireno's work while assimilating in his Dictionnary words which on the base of their formal and / or their semantic structure can not be considered as Catalan. Some of these words have been nevertheless accepted by 20th century lexicographers.